Challenges and Opportunities in Reporting Trauma-Related Research: A Case Study from Syria - Alothman, Muhammad Hussam; Tamer, Wardan Almir; Moscote-Salazar, Luis Rafael; Ghosh, Amrita; Pal, Ranabir; Agrawal, Amit (Indian Journal of Neurotrauma, 2019)
Background Reporting war trauma research is an arduous mission because it needs accurate data collection and it is considered a tough task as a result of the emergent management nature of such injuries which implies neglecting the medical records. The conflict in Syria involved extreme numbers of war trauma injuries which might be implemented in creating a prototype for preparedness plans which might decrease the number of casualties or, at the very least, minimize the damage for future combat trauma injuries.Material and Methods Data were sought from the Department of Surgery at Hama National Hospital on war injuries during 2017 to make a research paper on the experience of Hama National Hospital, Syria, a nonmilitary hospital that treats war injuries.Results In 2017, 2,912 war injury patients were admitted to the Hama National Hospital, among which 683 (23.455%) were dead-on-arrival and the remaining 2,229 patients (76.545%) were treated in emergency room (ER). Among those treated in the ER, shrapnel was the first cause of injury reported in 1,165 patients (52.26%), followed by bullets in 585 (26.24%) and trauma in 316 (14.17%). There were no data on the age of patients, the initial investigations done, the Glasgow Coma Scale score on admission, the primary management, the follow-ups, or even the mortality rates among hospitalized patients. The data were insufficient to write a well-balanced research paper because of the scarcity of information extracted from the medical records.Conclusion Doing a research in conflict settings requires more attention to detail and the medical staff should be trained to take care of the medical records because even if it seems inappropriate to spend time on recording in conflict atmospheres, making well-established recordings would contribute to the enhancement of the health care management of future war trauma injuries.
Keywords: injuries; health services research; armed conflicts; retrospective studies; Syria